Molecular typing of canine parvovirus type 2 by VP2 gene sequencing and restriction fragment length polymorphism in affected dogs from Egypt - Magouz, Asmaa; El-Kon, Ismail; Raya-Álvarez, Enrique; Khaled, Enas; Alkhalefa, Noura; Alhegaili, Alaa S.; El-khadragy, Manal F.; Agil, Ahmad; Elmahallawy, Ehab Kotb (Frontiers in Microbiology, 2023)
Introduction: Canine parvovirus-2 (CPV-2) is one of the most common infectious diseases in dogs characterized by severe gastroenteritis, vomiting, and bloody diarrhea. Little information is available about this topic in Egypt, particularly in the Delta region. This study reports the prevalence and molecular analysis of CPV-2 variants collected from El-Gharbia and Kafrelsheikh governorates in the Delta of Egypt. Methods: In this study, 320 rectal swabs were collected from infected domestic dogs from two districts in delta Egypt. The samples were investigated by rapid immunochromatographic test and polymerase chain reaction for detection the prevalence of CPV-2 variants. The genetic characterization was performed using restriction fragment length polymorphism (RFLP) analysis and partial VP2 gene sequence. Results and discussion: The viral antigen was detected in (264/320; 82.5%) of samples by IC test, while PCR was found more sensitive by detecting (272/320; 85%) positive samples. The RFLP technique using MboII restriction enzyme was successfully used for the differentiation of CPV-2c antigenic variants from CPV-2a/2b strains. Interestingly, the molecular and phylogenetic analysis revealed that both CPV-2a and CPV-2c are circulating in the study area. Deduced amino acid sequence analysis showed changes at residue (N426E) and residue (T440A).: Our results indicated that CPV-2 is prevalent among dogs in Egypt, and therefore further molecular and epidemiological studies of CPV-2 are warranted.